2012
DOI: 10.1155/2012/205131
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Encephalopathies in Adults and Childhood

Abstract: Epileptic encephalopathies are motor-mental retardations or cognitive disorders secondary to epileptic seizures or epileptiform activities. Encephalopaties due to brain damage, medications, or systemic diseases are generally not in the scope of this definition, but they may rarely accompany the condition. Appropriate differential diagnosis of epileptic seizures as well as subclinical electroencephalographic discharges are crucial for management of seizures and epileptiform discharges and relative regression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 119 publications
(106 reference statements)
0
9
0
1
Order By: Relevance
“…Epileptic encephalopathies (EE) are a heterogeneous group of epilepsy syndromes ( 14 , 15 ) in which epileptic activity leads to progressively greater levels of cognitive and behavioral impairment as it would be expected only as a result of the underlying structural or genetic pathology. According to ILAE guidelines (International League Against Epilepsy), common EE syndromes with characteristic electroclinical manifestations are Lennox-Gastaut Syndrome (LGS), Dravet Syndrome (DS), West Syndrome (WS) and EE with continuous spike-and-wave during sleep (CSWS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epileptic encephalopathies (EE) are a heterogeneous group of epilepsy syndromes ( 14 , 15 ) in which epileptic activity leads to progressively greater levels of cognitive and behavioral impairment as it would be expected only as a result of the underlying structural or genetic pathology. According to ILAE guidelines (International League Against Epilepsy), common EE syndromes with characteristic electroclinical manifestations are Lennox-Gastaut Syndrome (LGS), Dravet Syndrome (DS), West Syndrome (WS) and EE with continuous spike-and-wave during sleep (CSWS).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of EE patients develop refractory epilepsies and suffer from relapsing seizures of heterogeneous semiologies. Frequent hospitalization associated with the need for extended medical and nursing care place major social, interpersonal, and economic burden on patients, caregivers and society ( 14 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pgp function was first found to be inhibited by Ca 2+ -channel blocker verapamil and hence it has been used to tackle drug resistance epilepsy [61,62]. According to a few clinical case reports, patients not responding to various combination treatments of drug showed significant reduction of seizures when verapamil was coadministered with antiepileptic drugs [63,64]. Previous studies have reported that verapamil was used in patients with refractory epilepsy and showed effects by inhibiting Pgp [65,66].…”
Section: Direct Pgp Inhibitionmentioning
confidence: 99%
“…Кроме того, описано существование не-скольких аллельных вариантов ЭЭ, возникающих при мутациях в одном и том же гене. Так, например, мутации в гене SCN1A могут приводить к возникно- вению не только cиндрома Драве, но и фебрильных судорог 3А-типа, гемиплегической мигрени и эпи-лепсии из группы генерализованных эпилепсий с фебрильными судорогами плюс [19]. C другой сто-роны, у больных с клиническими проявлениями синдрома Драве обнаруживаются мутации и в дру-гих генах: SСN9A, PCDH19, GABRG2.…”
Section: наследственные варианты ээunclassified